Electronic Journal Database Usage Factors by the educators of Dr. Soetomo - Perdana, Kresna Putra; Prihatin, Silverius Djuni (Record and Library Journal, 2021)
Background of the study: The availability of information in libraries such as e-books and e-journals are scientific works that should belong to academic libraries. Within a year, the electronic journal database consortium program that was subscribed and provided by the Unitomo library was still underutilized. Purpose: This study aims to analyze the policy of strengthening the role of libraries in supporting scientific communication at IAIN Curup. Method: This study uses a quantitative method with a questionnaire survey using the smart PLS program. This study uses the TAM model with external variables. Findings: The results showed that the coefficient of determination (R-squared) of the independent variable over the dependent variable Y (using electronic journal database as large as 0.701 or in a percentage of 70.1%) was influenced by l ’self-efficacy, complexity, time constraints and reasons for promotion. While the results of the simultaneous significance test have a positive and significant influence on the independent variables of the dependent variable, namely the use of the electronic journal database (Y) can be influenced simultaneously or together and significantly the complexity of personal effectiveness variables. Conclusion: time limits and reasons for promotion together. Influences the level of use of the electronic journal database by the teaching staff of Dr. Soetomo.